2017
DOI: 10.1097/meg.0000000000000755
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-based hepatitis C therapy in a safety net hospital: access, efficacy, and safety

Abstract: An acceptable SVR rate is achievable in a safety net patient population. Addressing the barriers to care will be paramount when using direct-acting antivirals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 28 publications
1
8
1
Order By: Relevance
“…Our study population suffered a loss to follow-up rate of 5%, only marginally higher than the 2.5–3.8% reported in non-indigent real-world studies [ 9 11 ] and comparable with the 5–15% reported in previous studies of IFN-based therapy in indigent populations [ 24 , 28 , 31 ]. Interestingly, among those lost to liver clinic follow-up, approximately 1 in 5 were subsequently seen by their primary care providers within the same healthcare system.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Our study population suffered a loss to follow-up rate of 5%, only marginally higher than the 2.5–3.8% reported in non-indigent real-world studies [ 9 11 ] and comparable with the 5–15% reported in previous studies of IFN-based therapy in indigent populations [ 24 , 28 , 31 ]. Interestingly, among those lost to liver clinic follow-up, approximately 1 in 5 were subsequently seen by their primary care providers within the same healthcare system.…”
Section: Discussionsupporting
confidence: 68%
“…Of note, both prior studies were conducted in states that offer expanded Medicaid, through which access to HCV treatment is possible for a larger proportion of low-income patients. Data shows that the burden of HCV is 7.5% higher in those with Medicaid compared to commercial insurance [ 24 ]. In states without expanded Medicaid, such as Texas, access to HCV treatment is limited due to a smaller proportion of low-income patients being granted Medicaid coverage, as well as the existence of restrictions on treatment eligibility (i.e., advanced liver disease, negative toxicology screens, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…The Global Burden of Disease Liver Cancer Collaboration stated that most cases of liver cancer can be prevented through various therapies, including antiviral treatment for HCC associated with viral diseases . For HCV, the recent advent of interferon (IFN)‐free direct‐acting antivirals (DAAs) has introduced highly effective (>80%‐90% cure rate) and well‐tolerated treatment, even for patients with advanced liver disease, including HCC . It has been shown to reduce HCC risk and does not increase the risk of HCC recurrence .…”
mentioning
confidence: 99%
“…Several clinical variables that may explain different response to antiviral treatment among patients with HCV infection have been suggested. 18-21 By univariate and multivariate analyses, we found no relationship between patients’ baseline characteristics and SVR rates. These data provide further evidence that baseline characteristics (such as HCV genotype, sex, fibrosis status, HIV coinfection, prior treatment failure, and HCV RNA) have less impact on SVR rates with DAA-based antiviral therapy.…”
Section: Discussionmentioning
confidence: 69%